Kemampuan Gerak Dasar dan Olahraga dalam Pendidikan Jasmani Anak Usia Dini di TK Harapan Bunda Kabupaten Seluma - Ovi Arieska Mefa; Dzikra Fadillah Alfarizka; Tia Amelia (UIN Fatmawati Sukarno Bengkulu, 2026)
This study aims to examine the basic movement materials and the introduction of various sports in physical education for early childhood at TK Harapan Bunda, Seluma Regency. This research used a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The results show that the learning materials include locomotor, non-locomotor, and manipulative movements. Sports are introduced through simple and play-based activities such as gymnastics and ball games. The learning process is implemented through demonstration and direct practice. Despite limitations in facilities and differences in children's abilities, teachers are able to adapt effectively. This learning has a positive impact on children's motor and social development. In conclusion, the implementation of basic movement and sports learning in early childhood education has been effective and contributes positively to children's development.